eCM 2022
DOI: 10.22203/ecm.v044a02
|View full text |Cite
|
Sign up to set email alerts
|

Tissue engineering approaches for the repair and regeneration of the anterior cruciate ligament: towards 3D bioprinted ACL-on-chip

Abstract: The anterior cruciate ligament (ACL) is the most frequently injured ligament in the knee. The current method to treat the injured ligament is reconstruction using autografts and allografts. Reconstruction requires the regeneration of ligament, bone and their interface to ensure proper recovery. Recently, researchers have focused on using tissue-engineered scaffolds made of synthetic materials and biomaterials —such as collagen, decellularised tissues, silk and synthetic polymers produced following different ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…[57] In vivo degradation experiments revealed that silk proteins were completely hydrolyzed within 2 years and lost their tensile strength within 1 year, indicating that the gradual degradation of silk proteins permits a smooth transfer of mechanical load from the scaffold to the new tissue block. [58,59] Gao et al conducted in vitro degradation experiments on silk pro-tein scaffolds and found that even after eight weeks of incubation, the scaffolds maintained excellent mechanical properties and structural integrity. Furthermore, rabbit in vivo degradation experiments demonstrated that scaffold degradation was accompanied by the growth of fibrous tissue and that the structure eventually collapsed as degradation products were progressively absorbed, and they noted that connective tissue filled the Scaffold 12 weeks after implantation.…”
Section: Silk Protein-based Scaffoldmentioning
confidence: 99%
See 1 more Smart Citation
“…[57] In vivo degradation experiments revealed that silk proteins were completely hydrolyzed within 2 years and lost their tensile strength within 1 year, indicating that the gradual degradation of silk proteins permits a smooth transfer of mechanical load from the scaffold to the new tissue block. [58,59] Gao et al conducted in vitro degradation experiments on silk pro-tein scaffolds and found that even after eight weeks of incubation, the scaffolds maintained excellent mechanical properties and structural integrity. Furthermore, rabbit in vivo degradation experiments demonstrated that scaffold degradation was accompanied by the growth of fibrous tissue and that the structure eventually collapsed as degradation products were progressively absorbed, and they noted that connective tissue filled the Scaffold 12 weeks after implantation.…”
Section: Silk Protein-based Scaffoldmentioning
confidence: 99%
“…[56,57] In vivo degradation Completely hydrolyzed within 2 years, lost tensile strength within 1 year. [58,59] In vitro degradation Maintained mechanical properties and structural integrity after 8 weeks. [60] Degradation experiments Remaining weight of randomly aligned scaffold was 74.52% ± 11.34%, aligned scaffolds was 75.89% ± 6.13%.…”
Section: Silk Silk Protein Characteristicsmentioning
confidence: 99%
“…The current gold standard is to substitute the ruptured ACL with ligament autografts most often harvested from the so-called Hamstring, or from the quadriceps muscles or using the patellar ligament [ 19 ]. However, autografts from the Hamstring muscles are limited and, due to the fact that a higher incidence of tunnel widening and electromechanical delay in the knee flexors happen after autologous reconstructions [ 13 , 20 ], there is an urgent need for tissue-engineered ligament grafts with a special attention to the different zoning at the future bone-transition area [ 21 ]. This is because the current gold standard (Hamstring) uses only tendinous tissue, but it has been shown that its bony integration remains insufficient [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our systematic review focused on bioprinting of cartilage, bone, blood vessels, and composite tissues of bone and cartilage (osteochondral) and vascularized bone 1 . For reviews on bioprinting of other musculoskeletal tissues such as skeletal muscle, tendon and ligament please refer to those by Samandari et al 2 , Khalak et al 3 and Bakirci et al 4 respectively. 3D bioprinting is a relatively new field, with the first example being reported in 2003 5,6 .…”
mentioning
confidence: 99%
“…Looking at the outcome metrics used, measurement of cell viability was the predominant assay across all tissues 4 . The next most common analysis was to look at gene expression, defining increases or expression of genes relevant to each type.…”
mentioning
confidence: 99%